THE EFFECT OF OPERATING, LEVERAGE, SALES GROWTH AND WORKING CAPITAL FLOW OF PROFITABILITY WITH FIRM SIZE AS MODERATING VARIABLES ON MANUFACTURING COMPANIES LISTED ON THE IDX PERIOD 2008-2017 - siahaan, junaidi (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of the following research is to analyse the effect of operating cash flow, leverage, sales growth and working capital turnover simultaneously and partially to profitability and to determine and analyse whether firm size variables as moderating variables can strengthen and weaken the relationship between operating cash flow, leverage, growth working capital sales and turnover in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX). This type of research uses causal design which is useful for analysing the causal relationship between one variable with another variable and the object of this research is all manufacturing companies in the Indonesia Stock Exchange (IDX). The data used are secondary data obtained from IDX and the source of each company's site for the period 2008-2017. Sampling using purposive sampling method, obtained a sample of companies as many as 56 companies from 149 population companies with a total observation of 560. The method of data collection used is documentation techniques. The method of data analysis uses descriptive statistical methods, data panel regression analysis and interactive tests to moderate panel data variables, using the Eviews software tool. The results of this study indicate that simultaneously operating cash flow, leverage, sales growth and working capital turnover are significant to profitability. Partial testing shows that operating cash flow and sales growth on profitability have a significant positive effect, while leverage and working capital turnover have a positive and not significant effect on profitability. Moderating testing with interaction test shows that company size is not proven / moderating as a moderating variable that can moderate the relationship of operating cash flow, leverage and working capital turnover with profitability, while firm size is proven as a moderating variable of sales growth to profitability in manufacturing companies listed in Indonesia Stock Exchange (IDX).